2022
DOI: 10.3390/en15030828
|View full text |Cite
|
Sign up to set email alerts
|

Smart Distribution Network Situation Awareness for High-Quality Operation and Maintenance: A Brief Review

Abstract: In order to meet the requirements of high-tech enterprises for high power quality, high-quality operation and maintenance (O&M) in smart distribution networks (SDN) is becoming increasingly important. As a significant element in enhancing the high-quality O&M of SDN, situation awareness (SA) began to excite the significant interest of scholars and managers, especially after the integration of intermittent renewable energy into SDN. Specific to high-quality O&M, the paper decomposes SA into three st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 120 publications
0
19
0
Order By: Relevance
“…Te optimization work contains objective functions [19][20][21][22][23][24][25][26][27] and constraints [28][29][30][31][32][33][34][35][36]. Also, to apply optimization to the distribution network, smart technologies [37][38][39][40][41] and telecommunications equipment [42][43][44][45] should be used in the network. In the objective function of the proposed problem, the minimization of the voltage deviation from the desired value and the minimization of the distribution network losses are expressed, respectively, to achieve the goals of improving the network voltage profle and reducing losses.…”
Section: Mathematical Model Of the Proposed Problemmentioning
confidence: 99%
“…Te optimization work contains objective functions [19][20][21][22][23][24][25][26][27] and constraints [28][29][30][31][32][33][34][35][36]. Also, to apply optimization to the distribution network, smart technologies [37][38][39][40][41] and telecommunications equipment [42][43][44][45] should be used in the network. In the objective function of the proposed problem, the minimization of the voltage deviation from the desired value and the minimization of the distribution network losses are expressed, respectively, to achieve the goals of improving the network voltage profle and reducing losses.…”
Section: Mathematical Model Of the Proposed Problemmentioning
confidence: 99%
“…Green money, often known as sustainable or climate financing, has many meanings. Green finance refers to providing financial support for projects with positive effects on the ecosystem (Ge et al 2022 ). Alternatively, “climate finance” refers to funds explicitly allocated for initiatives that mitigate global warming.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Energy Outlook, 2030(Zang et al, 2022, energy power plants account for more than 70% of global energy consumption. Authorities have stepped up their sustainability responsibilities because of the effects of climate change (Ge et al, 2022). And over 800 million individuals will be affected by the "environmental movement" by March 2019, when 1046 authorities in 30 states proclaim it (Iqbal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of every economic system is to raise GDP without sacrificing emissions standards. Many studies (Walker, 2020;Ge et al, 2022) show a direct relationship between economic growth and sustainable energy use. Studies have shown that information and communication technology can help to minimize energy consumption in different areas, such as construction, storage, and transportation, by offering practical technologies (Wang H. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%